CT angiography-based collateral flow and time to reperfusion are strong predictors of outcome in endovascular treatment of patients with stroke. (23rd September 2016) - Sallustio, Fabrizio; Motta, Caterina; Pizzuto, Silvia; Diomedi, Marina; Giordano, Angela; D'Agostino, Vittoria Carla; Samà, Domenico; Mangiafico, Salvatore; Saia, Valentina; Legramante, Jacopo Maria; Konda, Daniel; Pampana, Enrico; et al.
Abstract : Background: Collateral flow (CF) is an effective predictor of outcome in acute ischemic stroke (AIS) with potential to sustain the ischemic penumbra. However, the clinical prognostic value of CF in patients with AIS undergoing mechanical thrombectomy has not been clearly established. We evaluated the relationship of CF with clinical outcomes in patients with large artery anterior circulation AIS treated with mechanical thrombectomy. Methods: Baseline collaterals of patients with AIS (n=135) undergoing mechanical thrombectomy were independently evaluated by CT angiography (CTA) and conventional angiography and dichotomized into poor and good CF. Multivariable analyses were performed to evaluate the predictive effect of CF on outcome and the effect of time to reperfusion on outcome based on adequacy of the collaterals. Results: Evaluation of CF was consistent by both CTA and conventional angiography (p<0.0001). A higher rate of patients with good collaterals had good functional outcome at 3-month follow-up compared with those with poor collaterals (modified Rankin Scale (mRS) 0–2: 60% vs 10%, p=0.0001). Patients with poor collaterals had a significantly higher mortality rate (mRS 6: 45% vs 8%, p=0.0001). Multivariable analyses showed that CF was the strongest predictor of outcome. Time to reperfusion had a clear effect on favorable outcome (mRS ≤2) in patients with good collaterals; in patients with poor collaterals this effect was only seen when mRS ≤3 was considered an acceptable outcome. Conclusions: CTA is a valid tool for assessing the ability of CF to predict clinical outcome in patients with AIS treated with mechanical thrombectomy. Limiting time to reperfusion is of definite value in patients with good collaterals and also to some extent in those with poor collaterals.